Niveles de burnout y estrategias de afrontamiento en docentes de educación superior. - Alvarado, S.M.C. (2020)
Introduction: Health educators and general workers in the sector are among the people vulnerable to stress and burnout Objective: To discuss, based on the scientific literature, burnout levels and coping strategies in higher education professors. Methods: Systematic review of articles published between 2010 and 2018 in the databases EBSCO host, SCIELO, ERIC, SCIENCE DIRECT, SCOPUS, REDALYC, DOAJ, and LILACS. In the search strategy, the Preferred Reporting Items for Systematic Review and Meta-Analyzes (PRISMA) flowchart was used. Eighteen articles (in Spanish, Portuguese, and English) were reviewed after applying the inclusion and exclusion criteria. Conclusions: It is not clear if burnout exists in higher education professors. High levels of exhaustion and depersonalization are slightly associated with high work commitment. Job stress and high level of exhaustion are associated with less job satisfaction. Relationship between high level of exhaustion is associated with younger professors with less experience. Exhaustion is associated with academic factors such as teaching hours. Burnout is associated with research activities. Increased stress is associated with an employment condition as contracted. No significant relationship was found between burnout and feelings of self-efficacy or teaching performance, or between emotional fatigue and occupational satisfaction. The strategies for dealing with stress that teachers use are those focused on solving the problem, seeking help or social support, and positive revaluation.